Ant nest-like hierarchical porous imprinted resin-dispersive solid-phase extraction for selective extraction and determination of polychlorinated biphenyls in milk. (16th April 2023) - Lu, Yanke; Shen, Qi; Zhai, Chengcheng; Yan, Hongyuan; Shen, Shigang
Graphical abstract: Highlights: Ant nest-like porous imprinting resin (IL-MIPPR) was fabricated for the first time. IL-MIPPR has an economical, high yield, hierarchical porous, and large surface area. IL-MIPPR − DSPE completed the extraction process of five PCBs in milk in about 10 min. An IL-MIPPR − DSPE − GC–MS/MS was developed for the determination of PCBs in milk. Abstract: Polychlorinated biphenyls (PCBs) are persistent toxic, organic chemicals that tend to accumulate in the food chain. This study reports the rapid and selective extraction and determination of PCBs (PCB81, 153, 105, 126, and 157) in milk samples by a dispersive solid-phase extraction (DSPE) coupled with gas chromatography-tandem mass spectrometry (GC–MS/MS). An ionic liquid-molecularly imprinted porous resin (IL-MIPPR) as a DSPE adsorbent was synthesized from m -aminophenol, formaldehyde, and 2, 2′-benzidinedisulfonic acid as the monomer, crosslinker, and virtual template, respectively. The IL-MIPPR had a fast mass transfer (1.0 min) and good selectivity (imprinting factors of 1.8–3.0). The IL-MIPPR − DSPE − GC–MS/MS method exhibited good linearity (R 2  ≥ 0.9995), the limit of detections (LODs) < 0.6 pg/g, and the recoveries ranged from 82.8 % to 106 % with relative standard deviations ≤ 6.6 %. This method is thus better than previously reported methods in terms of the LOD, the adsorbent dosage, and the extraction time.